Multifunctional, biocompatible and pH-responsive carbon nanotube- and graphene oxide/tectomer hybrid composites and coatings. Issue 23 (10th February 2017) - Garriga, Rosa; Jurewicz, Izabela; Seyedin, Shayan; Bardi, Niki; Totti, Stella; Matta-Domjan, Brigitta; Velliou, Eirini G.; Alkhorayef, Mohammed A.; Cebolla, Vicente L.; Razal, Joselito M.; Dalton, Alan B.; Muñoz, Edgar
Abstract : pH-Responsive carbon nanotube- and graphene oxide/tectomer hybrids and coatings, with vast possibilities for technological and biomedical applications. Abstract : Here we present a route for non-covalent functionalization of carboxylated multi-walled carbon nanotubes and graphene oxide with novel two-dimensional peptide assemblies. We show that self-assembled amino-terminated biantennary and tetraantennary oligoglycine peptides (referred to as tectomers) effectively coat carboxylated multi-walled carbon nanotubes and also strongly interact with graphene oxide due to electrostatic interactions and hydrogen bonding as the driving force, respectively. The resulting hybrids can be made into free-standing conducting composites or applied in the form of thin, pH-switchable bioadhesive coatings onto graphene oxide fibers. Monitoring of cell viability of pancreatic cell lines, seeded on those CNT hybrids, show that they can be used as two- and three-dimensional scaffolds to tissue engineer tumour models for studying ex vivo the tumour development and response to treatment. This highly versatile method in producing pH-responsive hybrids and coatings offers an attractive platform for a variety of biomedical applications and for the development of functional materials such as smart textiles, sensors and bioelectronic devices.